Biogenetic Origin of the d-Isoleucine and N-Methyl-l-Alloisoleucine Residues in the Actinomycins - Yajima, Takehiko (1976)
Studies with (14)C-labeled isoleucine stereisomers have established that l-alloisoleucine, d-alloisoleucine, and d-isoleucine may function as precursors for the biogenesis of d-isoleucine and N-methyl-l-alloisoleucine residues in actinomycin. l-[(14)C]isoleucine appears to be employed chiefly for d-alloisoleucine (and N-methylisoleucine [?] formation); however, its role in the biosynthesis of d-isoleucine and N-methylalloisoleucine remains unclear. The potential pathway of biosynthesis of d-isoleucine and N-methyl-l-isoleucine is discussed.